ZC3H15 suppression ameliorates bone cancer pain through inhibiting neuronal oxidative stress and microglial inflammation - Li-Quan Huang; Ting-Xuan Yan; Bao-Sheng Wang; Hao Li; Nai-Bao Zhou (Neoplasia: An International Journal for Oncology Research)
Background: Patients with advanced-stage malignancies often endure unbearable pain, partly due to the incomplete understanding of its molecular mechanisms. Zinc finger CCCH-type containing 15 (ZC3H15) is a highly conserved eukaryotic protein involved in various cellular processes, including tumor growth and inflammation. However, its impact on cancer-induced pain, especially the underlying mechanisms, remains largely unknown. Methods: To evaluate the expression of ZC3H15 in cancer-induced pain, we used microcomputed tomography (MicroCT), immunoblotting, co-immunoprecipitation (Co-IP), behavior tests, quantitative real-time polymerase chain reaction (qRT-PCR), and immunofluorescence assays in this investigation. Additionally, we used CCK8, cloning, and migration tests to examine the proliferation and migration of cancer cells. We also used transplantation tumor mouse model to investigate the course of the cancer cell growth. Finally, we looked into the biological processes linked to ZC3H15 using in vivo and in vitro ubiquitination detection, which was later verified. Results: In this study, we established a bone cancer pain (BCP) murine mouse model that impairs patients’ quality of life. Initially, we observed a significant increase in the expression of ZC3H15 in dorsal horn spinal cord tissues of BCP mice, along with severe oxidative stress and inflammation. Subsequently, we found that adeno-associated virus (AAV) expressing ZC3H15 short hairpin RNA (shRNA) (AAV-shZC3H15) to silence ZC3H15 in vivo significantly alleviated the progression of BCP in mice, improving nociceptive behaviors, independent of tumor burden and bone destruction. Subsequently, we made a novel discovery that ZC3H15 knockdown mice with BCP displayed improved neuronal oxidative stress and reactive oxygen species (ROS) generation in spinal cord tissues, which was confirmed in H2O2-treated mouse spinal cord neurons primarily through mediating the kelch-like ECH-associated protein 1 (KEAP1)/nuclear factor, erythroid 2-like transcription factor 2 (NRF2) pathway. Mechanistically, immunoblotting analysis revealed that ZC3H15 could maintain KEAP1 stability and thereby promote NRF2 ubiquitination and degradation under oxidative stress. Furthermore, the suppression of oxidative damage in neurons by ZC3H15 knockdown was significantly abolished upon the deletion of NRF2 expression, identifying the necessity of NRF2 for ZC3H15 in the mediation of BCP progression. Additionally, microglial activation and inflammatory response in spinal cord tissues of BCP mice were also attenuated by AAV-shZC3H15, which was verified in LPS-treated microglial cells in vitro by blocking the inhibitory protein κBα (IκBα)/nuclear factor κB (NF-κB) signaling pathway. Conclusions: Our results provide evidence that suppressing ZC3H15 can alleviate BCP by restricting neuronal oxidative stress and microglial activation, contributing to the improvement of nociceptive behaviors. Therefore, we concluded that ZC3H15 may be a potential target for the management of BCP.